Test de fonction rénal par isotopes. Une méthode de mésure de double isotope - Fog Pedersen, J.; Fog Pedersen, M.; Madsen, Paul O. (Nuklearmedizin - NuclearMedicine, 1971)
An accurate catheter-free technique for clinical determination simultaneouslyof glomerular filtration rate and effective renal plasma flow by means of radioisotopes has been developed. The renal function is estimated by the amount of radioisotopes necessary to maintain a constant concentration in the patient’s blood. The infusion pumps are steered by a feedback system, the pumps being automatically turned on when the radiation measured over the patient’s head falls below a certain preset level and turned off when this level is again readied.131I-iodopyracet was used for the estimation of effective renal plasma flow and125I-iothalamate estimation of the glomerular filtration rate. These clearances were compared to the conventional bladder clearances and good correlation was found between these two clearance methods (correlation coefficients 0.97 and.90 respectively). The advantages and disadvantages of this new clearance technique are discussed.